2021
DOI: 10.1002/edm2.285
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes mellitus (GDM) and adverse pregnancy outcome in South Asia: A systematic review

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 46 publications
0
25
1
1
Order By: Relevance
“…There is sufficient evidence that hyperglycemia during pregnancy can increase the risk of adverse pregnancy outcomes in mothers and their offspring in both the short and long term compared with normal pregnant women ( 1 ). A recent systematic review in South Asia showed that GDM is positively correlated with the occurrence of preeclampsia and has an impact on the occurrence of macrosomia, neonatal hyperglycemia, intrauterine growth retardation, stillbirth, and low birth weight ( 21 ). Some studies on LGA in China have shown that the incidence of LGA in patients with GDM ranges from 10–47.3% ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is sufficient evidence that hyperglycemia during pregnancy can increase the risk of adverse pregnancy outcomes in mothers and their offspring in both the short and long term compared with normal pregnant women ( 1 ). A recent systematic review in South Asia showed that GDM is positively correlated with the occurrence of preeclampsia and has an impact on the occurrence of macrosomia, neonatal hyperglycemia, intrauterine growth retardation, stillbirth, and low birth weight ( 21 ). Some studies on LGA in China have shown that the incidence of LGA in patients with GDM ranges from 10–47.3% ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, with the improvement of people's living standards and the development of medical technology, the incidence of GDM is getting higher and higher [ 3 ]. If GDM is not treated in time, it is very detrimental to the health of pregnant women and fetuses [ 4 6 ]. For pregnant women, GDM can increase the mother's possibility of developing high blood glucose, high blood pressure, and preeclampsia.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of developing PE in patients with GDM has been, up to date, widely studied [ 22 , 23 , 24 , 25 ]. PE and GDM share several risk factors, such as advanced maternal age, nulliparity, multiple pregnancy, ethnicity, and pregestational obesity.…”
Section: Introductionmentioning
confidence: 99%